ANALISIS PENGARUH RELIGIUSITAS DAN KEPERCAYAAN TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN JASA KEUANGAN SYARIAH (Studi Kasus pada BMT Beringharjo Cabang Ponorogo) - Hayatul Maemunah; Mohammad Nufaiz Mauludin (Universitas Darussalam Gontor, 2021)
Baitul Maal Wat Tamwil (BMT) is a form of non-bank sharia financial institutions whose business activities are based on the sharia system and included in (KJKS), namely sharia financial services cooperatives in Indonesia. The development of BMT in Indonesia has increased from year to year, as stated by Joelarso, General Chair of the Indonesian BMT Association Leadership Council,